KARAKTER PUTRI KENANGA DALAM LAKON KEANGKUHAN KARYA JONHAR SAAD DALAM PERTUNJUKAN DULMULUK DI PALEMBANG - Fitria Fitria; Sahrul Sahrul; Andar Indra Sastra (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT Character is temperament or habit. According to psychologist, character is a system of belief and habit that leads on an individual’s action. If knowledge about someone’s character can be known, how that someone will behave in certain conditions can also be known.The story of Princess Kenanga’s arrogance was started with the story of King and Queen of a country who had a very beautiful and smart daughter whose name’s Princess Kenanga. The beauty of this princess was renowned throughout the country but unfortunately this princess had arrogant and haughty natures.Princess Kenanga in the play “Keangkuhan (=Arrogance)” had evil characteristics because in her every appearance, she showed bad attitudes such as speaking harshly and doing action that’s not supposed to be done by a princess toward her folk and people. In the story of play “Keangkuhan (=Arrogance),” Princess Kenanga act abusively toward her folk.Keywords: Arrogance, Dulmuluk, Theater